Exploring the Functioning of Peer-to-peer Online Marketplace Platforms in France and Germany - Plenz, Rikarda Dorothea Ariane (Jihočeská univerzita, 2021)
Purpose - To study the habits and preferences of P2P online marketplace platform users overall and also with regard to national differences between a German and a French P2P platform in the context of the sharing economy and sustainable consumption. Methodology - A literature review identified specific items of interest related to sustainable consumption on P2P online marketplace platforms in the con-text of the sharing economy. A questionnaire was developed and self-administered by two groups of respondents: users of the German platform eBay Kleinanzeigen and users of the French platform leboncoin. Findings - There were some distinct differences between user preferences and habits of both platforms, as well as overarching findings about general use and motivations for P2P platform use. ANOVA results, Chi-square Tests of Independence, as well as t-tests identified amongst other things connections between sustainable intentions and higher use frequency, which in turn was connected to a stronger willingness to increase product life cycles by buying, selling, gifting or receiving broken things. Research limitations/implications - The samples for this study were assembled through snowball and convenience sampling. This limited sampling frame may affect the generalization of findings. For some of the hypotheses, the sample size was insufficient to obtain conclusive results. Practical implications - Both researchers on the topic of sustainable consumption in the sharing economy and managers the P2P platforms in question, as well as similar platforms or those who plan to implement similar platforms with the goal of sustainability, can benefit from the findings of this study. Value - This research contributes to the literature by studying user behaviour and preferences regarding P2P online marketplace platforms in the context of sustainable consumption.
Exploring the Functioning of Peer-to-peer Online Marketplace Platforms in France and Germany
Keywords: Sustainable consumption; sharing economy; collaborative consumption; glocalisation; peer-to-peer; P2P; Web 2.0; sustainability; consumer behaviour; Sustainable consumption; sharing economy; collaborative consumption; glocalisation; peer-to-peer; P2P; Web 2.0; sustainability; consumer behaviour